The Influence of Leader-Member Exchange Quality on the Exhibition of Organizational Citizenship Behavior: A Systematic Literature Review - Nootawee, Panida; Eakpamitsin, Wattana; Sakboonyarat, Tunyapat; wangthong, Chananchida (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This article aims to analyze and synthesize the influence of leader-member exchange (LMX) relationship quality on the exhibition of organizational citizenship behavior (OCB) using a systematic literature review and integrative analysis approach. Within the theoretical framework of social psychology and social exchange theory, the study examined academic articles and research papers published between 2016 and 2026 to ensure contemporary relevance. The methodology involves a systematic screening and content analysis of selected peer-reviewed sources. The findings, categorized by research objectives, demonstrate that high-quality LMX significantly engenders perceived organizational support (POS) and trust in leadership. These elements function as critical mediating mechanisms that lead to the manifestation of OCB across multiple dimensions, including altruism, sportsmanship, and conscientiousness. The conclusion underscores the imperative for leaders to cultivate and sustain exchange relationships characterized by mutual trust and respect. Such relationships enhance psychological commitment and drive extra-role behaviors, which are essential for organizational success and sustainability in the context of a smart ageing society.